EDA: EXAFS data-analysis software package - Kuzmin, Alexei (Wiley, 2021)
The EXAFS data-analysis software package EDA consists of a suite of programs running under a Windows operating system environment that is designed to perform all steps of conventional EXAFS data analysis such as extraction of the XANES/EXAFS parts of the X-ray absorption coefficient, Fourier filtering and EXAFS fitting using the Gaussian and cumulant models. The package also includes two advanced approaches which allow the reconstruction of the radial distribution function (RDF) from EXAFS based on the regularization-like method and the calculation of configuration-averaged EXAFS using a set of atomic configurations obtained from molecular-dynamics or Monte Carlo simulations.---- / / / ---- This is the preprint version of the following article: Alexei Kuzmin, EDA: EXAFS data-analysis software package, International Tables for Crystallography, Vol. I (2021), DOI: 10.1107/S1574870720003365, which has been published in final form at https://onlinelibrary.wiley.com/doi/full/10.1107/S1574870720003365.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; EXAFS